Analisis Implementasi Akad Mudharabah dan Sistem bagi Hasil pada Produk Simpanan Mudharabah : Studi Kasus : BPRS HIK Parahyangan - Amalia Marliani; Iwan Setiawan (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The purpose of this study is to analyze how the implementation of the mudharabah contract in mudharabah savings products at BPRS HIK Parahyangan. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews with the bank and direct observation of the operational process, as well as documentation of relevant secondary data. The main focus of the study is to examine the implementation of the principles of mudharabah and the profit sharing system applied in the savings product. The results of the study indicate that BPRS HIK Parahyangan has implemented the mudharabah contract in accordance with sharia principles. The bank acts as mudharib (fund manager), while the customer acts as shahibul maal (fund owner). The profit sharing system is determined based on an initial agreement and is distributed transparently based on the actual income obtained from fund management. This study is expected to improve the understanding and practitioners of sharia banking regarding the implementation of the mudharabah contract in banking products. In addition, the results of this study also contribute to the development of sharia financial literature and practices in Indonesia.